Determination of Volume of Capacitor Bank for Static VAR Compensator - Md. Ruhul Amin; Rajib Baran Roy (Institute of Advanced Engineering and Science, 2014)
In high voltage AC system, the system voltage and frequency change rapidly with the variation of load. The reactive power also changes with the variation of load which affects the system voltage therefore it is necessary to analyze the power system in order to determine system parameters and its variation under various load conditions. The capacitor bank size is determined by calculating existing reactive power and required reactive power in system for Static VAR Compensator (SVC) is focused in this paper. Base case load flow is used to analysis power system. After identifying low voltage buses, arbitrary caciptor back is imposed in bueses and results are checked whether it is met or not in the system demand level. Here MATLAB coding is used to find the low voltage affected bus and automated calculation of capacitor back size is done by MATLAB also. The proposed method of identification of low voltage buses and determination of capacitor bank are faster and easier than the conventional method.DOI:http://dx.doi.org/10.11591/ijece.v4i4.5803